GENDER-BASED FINANCIAL ACCESS IN LIBERIA'S FISHING INDUSTRY - Ninson, Jacqueline; Brobbey, Maame Kyerewaa (Applied Studies in Agribusiness and Commerce, 2025)
One essential component of the competitive operation of the fishing industry is the availability of finance. Access to finance is an important issue, but women's access to finance is more critical than men's. The study's objective is to emphasize gendered experiences with financial need, access to and selection of financial services, and service providers among Liberian actors in the fish industry. The study collected and analyzed data using a cross-sectional design. The research used primary data collection methods. Workers in Liberia's artisanal fishing value chain, both men and women, were the main population of interest. Respondents were chosen for the study using a two-stage sampling technique. Purposive sample of counties and random sampling of respondents were the two components of the two-stage sampling strategy. For the study, 278 men and women fish actors were selected as respondents using the random sampling technique. This study employed quantitative methodologies for data collection. From the findings, access to financial products is generally limited for fish actors. Nonetheless, some financial services and products are exclusive to either gender. Commercial banks are more accessible to men than to women. Because of their low income and educational attainment, women have limited access to commercial banks.